Energy-based viscoelastic model: a physical approach for material an elastic behavior by the bond graph approach. (January 2020) - Zanj, Amir; He, Fangpo; Breedveld, Peter C
Understanding the true nature of viscoelastic behaviors in multi-physical systems has always been a challenging issue in system dynamic investigations, as each existing physical subdomain of the system may follow a different attenuation pattern during the dynamic process. In this study, to generate a viscoelastic model suitable for multi-physical domain dynamic investigations, a physical combined viscoelastic model is proposed. To this aim, by means of the bond graph approach, an energy-based conventional viscoelastic model is first generated, and its embedded dispersive mechanisms are interpreted physically. By including the interpreted dissipative mechanisms into the relative subdomains of an elastic domain, an energy-based combined viscoelastic model is then proposed. The obtained simulation results indicate that the proposed viscoelastic model is able to capture a variety of viscoelastic behaviors in the system with respect to the true physical nature of the system.